Rest-frame UV properties of luminous strong gravitationally lensed Lyα emitters from the BELLS GALLERY Survey. Issue 1 (13th December 2019) - Marques-Chaves, R; Pérez-Fournon, I; Shu, Y; Colina, L; Bolton, A; Álvarez-Márquez, J; Brownstein, J; Cornachione, M; Geier, S; Jiménez-Ángel, C; Kojima, T; Mao, S; et al.
ABSTRACT: We present deep rest-frame UV spectroscopic observations using the Gran Telescopio Canarias of six gravitationally lensed Lyα emitters (LAEs) at 2.36 < z < 2.82 selected from the BELLS GALLERY survey. By taking the magnifications into account, we show that LAEs can be as luminous as L Lyα ≃ 30 × 10 42 erg s −1 and M UV ≃ −23 (AB) without invoking an AGN component, in contrast with previous findings. We measure Lyα rest-frame equivalent widths, EW_0 (Lyα), ranging from 16 to 50 Å and Lyα escape fractions, f_esc (Lyα), from 10 per cent to 40 per cent. Large EW_0 (Lyα) and f_esc (Lyα) are found predominantly in LAEs showing weak low-ionization ISM absorption ( EW 0 ≲ 1 Å) and narrow Lyα profiles (≲300 km s −1 FWHM) with their peak close (≲80 km s −1 ) to their systemic redshifts, suggestive of less scatter from low H i column densities that favours the escape of Lyα photons. We infer stellar metallicities of Z /Z⊙ ≃ 0.2 in almost all LAEs by comparing the P-Cygni profiles of the wind lines N v 1240 Å and C iv 1549 Å with those from stellar synthesis models. We also find a trend between M UV and the velocity offset of ISM absorption lines, such as the most luminous LAEs experience stronger outflows. The most luminous LAEs show star formation rates up to ≃180 M⊙ yr −1, yet they appear relatively blue (βUV ≃ −1.8 to −2.0) showing evidence of little dust attenuation [ E ( B − V ) = 0.10–0.14]. These luminous LAEs may be particular cases of young starburst galaxies that have had no time to form large amounts of dust. If so, they are ideal laboratories to study the early phase of massive star formation, stellar and dust mass growth, and chemical enrichment histories of starburst galaxies at high- z .